الجامعة الاسلامية العالمية بماليزيا وودورها فى تعليم اللغة العربية للناطقين بغيرها International Islamic University of Malaysia and Its Role in Teaching Arabic to Non-Native Speakers - (Alaa Hosni), علاء حسنى المزين (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
كان من أهم الآثار الإيجابية للصحوة الإسلامية التى عمت العالم الإسلامى بشكل ملحوظ منذ أوائل السبعينيات فى القرن العشرين زيادة إقبال الشعوب الإسلامية على تعلم اللغة العربية، وبدأ الاهتمام الحقيقى لجامعات العالم الإسلامى بتوفير مساقات متخصصة لهذا الغرض منذ أوائل الثمانينات، وكانت الجامعة الإسلامية العالمية بماليزيا التى أسست سنة 1983 من أنشط الجامعات فى هذا الصدد، وهو نشاط استلفت نظر الباحث إذ وجده يستحق الرصد والتوثيق العلمى، والمراجعة إذا اقتضت الضرورة لا بهدف الإشادة بالتجربة بل رغبة فى الإفادة والاستفادة من قبل المختصين من المهتمين بهذا الميدان الحيوى من ميادين خدمة اللغة العربية بل خدمة الإسلام، وحضارته نظرا للارتباط الوثيق بين اللغة العربية وهذا الدين الحنيف باعتبارها لغة كتابه الخالد، والمعلم الرئيس من معالم الهوية الإسلامية المميزة والصمود الحضارى. ***************************************************** One of the most positive effects of the Islamic awakening since the early seventies, in the twentieth century, which spread across the Islamic world in a significant manner, has been the increased Muslims’ interest in learning the Arabic language all over the world. There began a real interest in the universities of the Muslim world for the Arabic language by providing specialized courses for this purpose since the early eighties and the International Islamic University Malaysia established in 1983 has been the most active university in this regard. And this activity of the university drew the interest of the researcher who found it worthy of investigation and scientific documentation as well as of revision, if necessary, not in order to pay tribute to the experience, but for taking advantage and learning from specialists interested in this vital field of the fields of Arabic language service which is actually service of Islam and its civilization considering the strong connection between Islam and the Arabic language, the language of the Qur’Én , the most distinctive feature of Islamic identity and resilience of Islamic civilization.